Profile of HIV voluntary counseling and testing seropositive acceptors in Niger-Delta, Nigeria - Bernard Terkimbi Utoo; Priscilla M. Utoo; Chinedu C. Ekwempu (AOSIS, 2012)
Sub-Saharan Africa is most heavily affected by human immunodeficiency virus (HIV) infection worldwide. The infection is more commonly observed amongst vulnerable populations. The objective was to determine the profile of seropositive acceptors of HIV voluntary counseling and testing in Niger-Delta, Nigeria. Medical records of voluntary counseling and testing (VCT) acceptors at the Sacred Heart Hospital Obudu, Cross-River State, Nigeria, from January to July 2010 were reviewed. HIV antibody screening was done using two rapid ELISA tests. A total of 1269 VCT acceptors were screened for HIV antibodies out of which 134 (10.6%) tested positive. The age group 20-29 year old was more affected (41.0%). Average age of seropositive acceptors was however 31.21±8.8 years. Most of them 80 (59.7%) were females, married 61 (45.5%) and either had none or low level of formal education (61.2%). Traders constituted 25.4%, students 24.6%, farmers 20.9% among others. More females were married than the males (50.0% vs 38.9%) (P>0.05). There were more educated females than males (P>0.05). Those who had formal education were more likely to be either gainfully employed or seeking for one (P<0.001). HIV positivity was observed mostly among married, female adolescence/ young adult with either none or low level of formal education and engaged in commercial activities. Sustaining efforts towards women education, economic empowerment, and gender equity, modification of risky social lifestyle and VCT for HIV will be helpful in reducing HIV infection among the vulnerable groups.